The role of property tax in environmental protection - Cvjetković-Ivetić Cvjetana M. (Zbornik Radova: Pravni Fakultet u Novom Sadu, 2022)
In the paper the author considers the environmental characteristics of property tax. The aim of the paper is to present how this tax can be used in order to contribute to the protection of environment. Having in mind the fact that the ecological role of property tax in Serbia is quite modest, the author will try to answer whether there is room for further greening of the property tax by introducing new tax reliefs.